O-205 Aneuploidy induces proteotoxic stress and autophagy-mediated apoptosis in human preimplantation embryos. (6th August 2021) - Regin, M; De Deckersberg, E. Couvreu; Guns, Y; Verdyck, P; Verheyen, G; Van de Velde, H; Spits, C; Sermon, K
Abstract: Study question: Are aneuploid cells in human preimplantation embryos eliminated by apoptosis due to proteotoxic stress and autophagy-mediated apoptosis? Summary answer: Proteotoxic stress, autophagy and apoptosis are differentially activated in aneuploid embryos, showing that aneuploid cells are eliminated by these mechanisms during early human embryogenesis. What is known already: Aneuploidies are a common feature of human preimplantation embryos which could explain low success rates after in vitro fertilization (IVF). While most aneuploidies of meiotic origin are detrimental, transfer of euploid-aneuploid mosaic embryos can lead to healthy live-births. Moreover, the proportion of aneuploid cells are lower in blastocysts when compared to cleavage stage embryos. In the mouse, aneuploid cells are eliminated from the epiblast by autophagy-mediated apoptosis in a p53-dependent manner. We propose that in human embryos, aneuploidy causes chronic protein misfolding which leads to autophagy-induced apoptosis. Study design, size, duration: Eighty-one blastocysts that were diagnosed by PGT as euploid (n = 49) or uniformly combined abnormal (CA, n = 32), i.e. 2 or more chromosomes were abnormal in every cell, were warmed. Sixty-seven were suitable for trophectoderm (TE) biopsy, 54 biopsies were successfully tubed and sent for RNA-sequencing while the remainder of the embryos was fixed for immunostaining. Thirty-three day-3 embryos were overnight incubated in 0.5µM reversine allowed to develop into blastocysts and treated as the PGT embryos. Participants/materials, setting, methods: After TE biopsy, we live-stained the embryos with either Caspase-3/7 or 8 and subsequently fixed them. The biopsies underwent RNA-sequencing using the SMART-seqv4 and the fixed embryos were immunostained for LC3B, p62 (autophagy) and HSP70 (proteotoxic stress). Confocal imaging was performed using a Zeiss LSM800 confocal microscope and the presence of signal was quantified using the Zen Blue 2.0 and Arivis software. Main results and the role of chance: Forty-two percent of the embryos in which we induced aneuploidies using reversine developed into blastocysts, which is comparable to untreated embryos. After immunostaining, we observed that CA and reversine-treated (RT) embryos contained less cells than euploid embryos (median number of nuclei: 43.5, 47, 90, respectively). This correlates with a higher expression of apoptotic markers Caspase-3/7 in CA embryos (p = 0.0199) and Caspase-8 in both aneuploid groups (CA: p = 0.0085 and RT: p = 0.0394). Aneuploid embryos showed significantly increased HSP70 levels (median intensity per cell: euploid=165, CA = 313, RT = 400), LC3B (median puncta per cell: euploid=3.07, CA = 10.10, RT = 19.62) and p62 (median puncta per cell: euploid=17.60, CA = 30.53), suggesting increased proteotoxic stress and autophagy. Preliminary analysis of the RNA-sequencing data reveals enrichment for pathways such as the p53-pathway, protein secretion, TNFA signaling via NFkB and apoptosis, supporting the hypothesis of a link between aneuploidy and apoptosis. Limitations, reasons for caution: No functional tests e.g. with inhibitors of autophagy were carried out. RNA-sequencing was carried out on a small sample; we will expand this sample in the near future. Wider implications of the findings: This study shows for the first time the mechanism by which aneuploid cells are eliminated from the human preimplantation embryo, explaining how mosaic embryos can still lead to a healthy and genetically normal live birth. Trial registration number: not applicable